Nanoparticles in sustainable agriculture: enhancing nutrient use efficiency and abiotic stress resilience under climate change - Yingfen Yang; Chenghu Ye; Meiwei Zhao; Juan Li; Xiaoxia Zhang; Zihui Yang; Zhibo Yang; Uthman Balgith Algopishi; Waqar Ahmed (Plant Stress)
Climate change poses significant challenges to global agriculture, particularly by reducing nutrient availability and crop yields. Improving nutrient absorption and utilization is vital for sustainable agriculture, especially as the global population grows and food security becomes increasingly critical. Nanoparticles (NPs) offer a promising solution by enhancing plant nutrient uptake and stress tolerance through their unique physicochemical properties. This review examines the impact of various NP types: carbon-based, metal-based, and silicon-based applied through foliar sprays, soil amendments, or seed priming. These methods can improve nutrient solubility, root development, and crop productivity under abiotic stresses like drought, salinity, and heavy metal toxicity. We present recent case studies and experimental findings that highlight NPs’ dual role in enhancing macro/micronutrient bioavailability and mitigating stress via antioxidant activity and osmotic regulation. Nano-fertilizers also optimize nutrient use efficiency through controlled release, reducing environmental losses. However, challenges such as ecosystem safety, regulatory frameworks, and economic viability must be addressed for large-scale adoption. This review explores NPs potential to improve plant growth and nutrient uptake under climate change conditions, emphasizing the need for further research to ensure safe, sustainable implementation.